2006
DOI: 10.1007/s10800-006-9227-7
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Nafion®/conducting polymer composite in the PEM type fuel cells

Abstract: The present study focuses on the problem of using conducting polymers (CPs) in proton exchange membrane fuel cell technology. It covers the electrocatalytic properties of the CP/Pt composite, permeability of the CP film for H 2 , fixation of the compact CP film on the top of the Nafion Ò membrane and first results of its utilization in a fuel cell. The present results did not confirm a previously reported increase in CP/Pt composite electrocatalytic activity when compared to the commercially available carbon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Nevertheless, it still remains one order of magnitude lower than for pure Nafion Ò , which in FC technology is considered to be practically impermeable to hydrogen. This finding supports our previous results [28] that the CP composites with cathodically deposited Pt behave as 2D-electrodes. This is caused by the low permeability of PPy to fuel.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, it still remains one order of magnitude lower than for pure Nafion Ò , which in FC technology is considered to be practically impermeable to hydrogen. This finding supports our previous results [28] that the CP composites with cathodically deposited Pt behave as 2D-electrodes. This is caused by the low permeability of PPy to fuel.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, better control over mass-transport conditions is possible thanks to the possibility of defining a pulsating compositional double layer and of relaxing the double layer with zero-current periods. It is worth noting that, in the limit of long deposition periods at a given potential, multilayer M/PPy can be deposited [17]. For an insightful understanding of RPP in M/CP CECD, one should take into account that the current associated with each potential step contains both capacitive and faradaic contributions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, CECD leads to improved layer smoothness and homogeneity as well as finer Au grains in comparison with DC plating of similar materials. (i.b) Pt/PPy: sandwich composites, consisting of multiple electrodeposited PPy and Pt layers have been studied in [17]. (i.c) The growth of Ir, Pd, Pt and Ru/PPy composites has been described in [4], as obtained by polymerization in the presence of anionic Pt-group complexes that were reduced in a post-treatment, applied after completion of the polymer growth phase.…”
Section: Introductionmentioning
confidence: 99%
“…We reported that the nano-sized polypyrrole particles were mainly present near the surface rather than the internal space by controlling the concentration and diffusion time of pyrrole monomers [9]. In addition, some researches demonstrated that pyrrole monomers were diffused into and in situ polymerized at only one side of membrane by using diffusion method, thereby controlling the location of thin layer among two faces of Nafion matrix [10,11]. In the case of electrochemical synthesis compared to chemically oxidative polymerization, the rate, extent, and location of polymerization could be controlled by electrochemical conditions such as voltage or current as well as polymerization time and monomer concentration [12][13][14].…”
Section: Introductionmentioning
confidence: 99%